Assessing knowledge, practices, use and raising awareness of antibiotics and antibiotic resistance among dental patients before and after educational sessions : Raising awareness of antibiotics resistance - Farghaly, Mahassen; Badran, Amira; Keraa, Khaled (Brazilian Dental Science, 2021)
AbstractObjectives: Education and awareness-raising are global health policy tools to modify public behavior towards antibiotic resistance. Considering the high frequency of antibiotic use and self-medication in Egypt, together with the lack of an awareness agenda, our objectives were to assess the knowledge and practices related to antibiotic use and resistance among patients attending dental clinics, and to evaluate the changes in knowledge following a specially designed one to one educational session. Methodology: A convenience sample of 310 dental patients participated in this study. A modified questionnaire was used to assess knowledge and practices related to antibiotic use and resistance. Second-year dental students were trained to administer the questionnaire and to use the educational materials they designed to raise awareness. Following the education session, patients completed another similar questionnaire to assess the changes in their knowledge. Results: Increasing awareness of antibiotic resistance can be an effective way to address the antibiotic resistance crisis. More than half of the participants (55.6%) did not know whether antibiotics treat diseases caused by bacterial or viral infections. The majority of participants (85.5%) had taken antibiotics during the last year, and (50.5%) of them had taken the same antibiotic more than once. Higher educational levels of the participants were significantly associated with a higher level of knowledge. Statistically significant increases in the percentages of correct answers to all questions were observed after the educational session. Conclusion: The one to one educational session is an effective approach to address the antibiotic resistance crisis.Keywords Antibiotic use, antibiotic resistance, knowledge, practices, dental patients, awareness and education, SDGs.